(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The aim of this paper is to present the results of color change on the surface of natural maple wood and thermally treated maple wood with saturated water steam after UV irradiation in Xenotest 450 – simulation of natural wood aging process. Thermally untreated maple wood is white to light white-gray-yellow in color with coordinates L* = 86.6 ± 2.5; a* = 5.3 ± 1.7; b* = 19.3 ± 2.3 in CIE L*a*b* color space. The thermally treated maple wood is brown-red in color with coordinates L* = 65.3 ± 1.4; a* = 10.8 ± 1.3; b* = 19.3 ± 1.3. The surface of samples maple wood with moisture content w = 12% was irradiated in Xenotest 450 with a xenon lamp with UV radiation of 340 nm. Irradiation of the wood surface took place in the exposure cycle A1 for 7 days. While the irradiated surface of the thermally untreated maple wood darkened and acquired a brownish-yellow hue, the brownish-red hue of the thermally treated maple wood turned paled slightly. The total color difference ∆E* caused by UV radiation of thermally untreated maple wood is ∆E* = 15.2 and thermally treated maple wood is ∆E* = 10.8. A comparison of the simulated aging of thermally treated and thermally untreated maple wood in Xenotest 450 suggests that the overall color change of thermally treated wood is 28.9 % less.